Development of Wick Editor-Based Learning Media that Emphasizes the Creative Thinking Ability - Muhammad Dhaffa; Cahyono, Hendarto; Azmi, Rizal Dian (Mathematics Education Journal, 2024)
This development research aims to (1) Know the practicality of learning media based on the wick editor to be used in the learning process on the material of arithmetic rows and series (2) Know the response of students to the use of learning media in the classroom; and (3) Improve students' creative thinking skills to solve problems related to mathematics This research is a Research and Development (R&D) study with the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used interviews, validation, student response questionnaires, and student creative thinking ability questionnaires. Validation was carried out by academics and practitioners, as well as students' responses. The wick editor-based learning media developed was tested on 34 students of class VIII at senior high school. The results of material expert validation obtained an average score of 82.95% with very valid criteria. The practicality of the media obtained from the student response questionnaire obtained an average score of 90% with very practical criteria. The effectiveness of the media is obtained from the average results of the questionnaire of students' thinking skills with an average N-Gain score of 0.75 with a high category.